THE SYNERGY OF ISLAMIC FINANCE AND SUSTAINABLE DEVELOPMENT: MANAGEMENT INNOVATION IN PESANTREN-BASED AMIL ZAKAT INSTITUTIONS - Rahman, Holilur; Noor Aimi Mohamad Puad; Zaid Raya Argantara (Journal of Management and Islamic Finance, 2024)
This article explores the synergy between Islamic finance and sustainable development (SDGs) through. Meanwhile, a PUSKAS BAZNAS survey shows that 55% of zakat managers in Pesantren lack adequate managerial knowledge and skills. This article argues that Islamic finance and sustainable development synergize in offering practical insights for managers of Pesantren-based Amil Zakat Institutions. This research uses a qualitative approach with a literature review method, including an analysis of various literatures related to zakat management and sustainable development. The results of this article show that management innovation in Pesantren-based Amil Zakat Institutions can increase the effectiveness and efficiency of zakat management. Collaboration with other stakeholders expands the social impact of zakat. Additionally, training and developing managerial skills for zakat managers in Pesantren increase their capacity to manage funds more effectively. In conclusion, the synergy between Islamic finance and sustainable development can be realized through management innovation in Pesantren-based Amil Zakat Institutions in accordance with the principle of unrestricted public interest (al-maslahah al-mursalah). By enhancing managerial knowledge and skills, as well as leveraging technology and strategic collaboration, these Amil Zakat Institutions can play a crucial role in achieving the SDGs.